Teachers' perspectives on technology-mediated plurilingual practices: the TEMPLATE project - Enzo Boggio-López; Noelia Ruiz-Madrid (Research in Education and Learning Innovation Archives, 2024)
Plurilingual-inspired pedagogies show multiple potential benefits for teaching and learning languages and have therefore been strongly promoted by the European Union through various policies. Nonetheless, their implementation is not exempt from limitations and difficulties concerning teaching practices and availability of resources. Meanwhile, technology has long been seen as a chief factor in supporting and enhancing learning in the foreign language classroom, and it can now serve plurilingual-inspired pedagogies due to its flexibility and heterogeneity. The present study reports on the results obtained from a questionnaire completed by 306 teachers across Eu- rope, which explores their perspectives on the use of technology-mediated plurilingual practices. The survey has been designed ad hoc and then distributed among in- and pre-service teachers at pri- mary and secondary levels in 10 European countries. Our final aim is to investigate the integration of technology and plurilingual-inspired pedagogies in terms of awareness, use and training needs. Results indicate that almost half of the participants have implemented a digital-based activity that involved the use of different languages in the past, but yet claim that there is a scarcity of available information and resources. Further results look into the nature and characteristics of these plurilin- gual practices, as well as the role played by technology in such activities. Finally, teacher training implications derived from the results are discussed.